Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation terhadap Hasil Belajar Geografi - Achmad Taher; Sugeng Utaya; Syamsul Bachri (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to determine the differences in student geography learning outcomes taught with the group investigation model and those taught by conventional methods (discussion). This type of research is a quasi-experimental (quasi experimental). The study design used a pretest - posttest non-equivalent control group design. The data analysis used is the independent sample t-test value of the gain score with the help of the SPSS 16.0 for Windows application. The results showed that there were significant differences in geographic learning outcomes between the experimental class and the control class. The value of geography learning outcomes of students taught with group investigation models is better than the geography learning outcomes of students who are taught using conventional methods (discussion). This is because students who conduct investigations can understand geography learning material on the topic of coastal abrasion better than students who study conventionally.Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar geografi siswa yang diajar dengan model group investigation dan yang diajar dengan metode konvensional (diskusi). Jenis penelitian ini merupakan eksperimen semu (quasi experimental). Rancangan penelitian menggunakan pretest-posttest non-equivalent control group desain. Analisis data yang digunakan adalah uji independent sample t-test nilai dari gain score dengan bantuan aplikasi SPSS 16.0 for windows. Hasil penelitian menunjukkan adanya perbedaan hasil belajar geografi yang signifikan antara kelas eksperimen dan kelas kontrol. Nilai hasil belajar geografi siswa yang diajar dengan model group investigation lebih baik dibanding hasil belajar geografi siswa yang diajar dengan metode konvensional (diskusi). Hal ini disebabkan siswa yang melakukan investigasi dapat memahami materi pembelajaran geografi topik abrasi pantai lebih baik dibanding siswa yang belajar secara konvensional.